Defining and investigating occupational asthma: a consensus approach. Issue 6 (27th November 2006) - Francis, H C; Prys-Picard, C O; Fishwick, D; Stenton, C; Burge, P S; Bradshaw, L M; Ayres, J G; Campbell, S M; Niven, R McL
Abstract : Background: At present there is no internationally agreed definition of occupational asthma and there is a lack of guidance regarding the resources that should be readily available to physicians running specialist occupational asthma services. Aims: To agree a working definition of occupational asthma and to develop a framework of resources necessary to run a specialist occupational asthma clinic. Method: A modified RAND appropriateness method was used to gain a consensus of opinion from an expert panel of clinicians running specialist occupational asthma clinics in the UK. Results: Consensus was reached over 10 terms defining occupational asthma including: occupational asthma is defined as asthma induced by exposure in the working environment to airborne dusts vapours or fumes, with or without pre-existing asthma; occupational asthma encompasses the terms "sensitiser-induced asthma" and "acute irritant-induced asthma" (reactive airways dysfunction syndrome (RADS)); acute irritant-induced asthma is a type of occupational asthma where there is no latency and no immunological sensitisation and should only be used when a single high exposure has occurred; and the term "work-related asthma" can be used to include occupational asthma, acute irritant-induced asthma (RADS) and aggravation of pre-existing asthma. Disagreement arose on whether low dose irritant-induced asthma existed, but the panel agreed that if it did exist they would include it in the definition of "work-related asthma". The panel agreed on a set of 18 resources which should be available to a specialist occupational asthma service. These included pre-bronchodilator FEV1 and FVC (% predicted); peak flow monitoring (and plotting of results, OASYS II analysis); non-specific provocation challenge in the laboratory and specific IgE to a wide variety of occupational agents. Conclusion: It is hoped that the outcome of this process will improve uniformity of definition and investigation of occupational asthma across the UK.